Indo‑European ’ego’, Slavic ja = Runic ek, and Celtic Ø - P. Hamp, Eric (Slavia Centralis, 2020)
The paper gives a new account of the development of the first person singular pronoun in Indo-European languages, finding innovating areals (1) Anatolian *VK; (2) South-East Indo-European (Indo-Iranian, Armenian) *eg’-H-ém; (3) Greek, Latin, Venetic *eg’-(ó)H; (4) North I-E (Albanian, Baltic, Slavic, Germanic, Thracian, Tocharian) *eg’.